Contributions for a master plan for sustainable urban development of the green coast of metropolitan Lima and the Lima Callao megalopolis, Peru, with a vision to 2040 - Castillo-García, Rodolfo Francisco (2023)
The objective of this article is to make a conceptual and operational approach in order to propose contributions, reflections and technical proposals for the formulation and implementation of a Master Plan for Sustainable Urban Development of the Green Coast of Metropolitan Lima (PMCV)  and the Lima Callao Megalopolis, Peru, with Vision to 2040; based on academic research, personal reflections, professional experiences, and technical proposals of the Author linked to the urban plans of the Green Coast of Lima and Callao in the period 1960-2022, and on the sustainable urban development of the Costa Verde of the Lima Callao Megalopolis.This new Master Plan should be formulated with a criterion of planning continuity with the PMCV of 1995, emphasizing the integral nature of a master plan and not only the physical-landscape character of an urban plan; assuming the approach of “sustainable urban development planning”, considering the components of sustainable urban development; and emphasizing the fundamental role of the Costa Verde as a Megapolitan Coastal Park, and complementary, as an Alternative Megapolitan Road Axis.